The influence of organizational culture on the organizational performance of educational institutions (University of Technology as a model) - Raoof, Mohammed Imad (Journal of Economics and Administrative Sciences, 2021)
The organizational culture is an effective control mechanism that dictates the behavior of employees and according to their intellectual and social orientations, so it is considered a more powerful way to control employee orientations and determine their management according to organizational rules and regulations, as it was one of the most important factors determining the performance of organizations, while organizational performance is a measure of what the organization has achieved from the objectives of the scheme To ensure that it faces various changes and remains within the global competition, and to reach that it was necessary to identify the most prominent and most important research problems in knowing the extent of commitment to the application of organizational culture and its effects on the organizational performance of the Technological University and to know the relationship between the dimensions of organizational culture and its dimensions (relations, goals, rewards) And organizational performance and its dimensions (sources, results, goals). The questionnaire was relied on to obtain the required data and analyze it through the SPSS program, to reach the relationship between the two research variables. The questionnaire was presented to a sample of university employees with a number (81) questionnaire forms distributed between the director, branch chief and employees, The most important results are that the university should enhance its organizational performance through an organizational culture specific to the university in order to reach a goal I have a distinguished performance to achieve its goals, due to the importance and impact of organizational culture on organizational performance to reach the university's goal in achieving integration between human relations and the regulations and rules governing the university's work for all its employees and this is evident in its reflection on university students, students and graduates